Study on static strength of Q690 built-up K-joints under axial loads. (May 2023) - Jiang, J.; Ye, M.; Chen, L.Y.; Zhu, Z.W.; Wu, M.
Abstract: In this paper, the ultimate bearing capacity and failure mod of Q690 built-up K-joints is numerically studied. Two benchmark finite element (FE) models are firstly validated by the test results. After that, a parametric study of 192 FE models is organized to investigate effect of geometrical parameters of the Q690 built-up K-joints such as brace diameter-to-chord width ratio ( β ), width-to-thickness ratio of chord (2 γ ), thickness ratio of brace to chord ( τ ) and chord preloading ( n ) on the ultimate bearing capacity. It is found that plastic failure or local buckling of chord are the two main failure modes. Finally, the FE modeling results are compared with Chinese design code, Eurocode as well as CIDECD design guide. β, 2 γ, τ and n have different effects on the ultimate bearing capacity of the K joints. The ultimate bearing capacity of the joints increases significantly with the increase of β . Positive effect of 2 γ and n on the ultimate bearing capacity also can be observed. The ultimate bearing capacity of the joints has little correlation with τ . A more accurate prediction formula for ultimate bearing capacity of Q690 built-up K joints is proposed and it can give better prediction for ultimate bearing capacity of Q690 built-up K joints.